DEKONSTRUKSI RELASI MANUSIA DAN ALAM DALAM BUKU BUMI YANG TAK DAPAT DIHUNI PERSPEKTIF MICHEL FOUCAULT - Muhammad Bima Sena; Tri Utami Oktafiani (Jurnal Bastra (Bahasa dan Sastra), 2026)
This study examines the deconstruction of the relationship between humans and nature in David Wallace-Wells's book *The Uninhabitable Earth*, using Michel Foucault's perspective. The aim is to uncover how the text deconstructs the anthropocentric discourse that has long dominated human perspectives on nature. The method used is Foucaultian discourse analysis with a qualitative approach, incorporating a deconstructive analysis of the human-nature binary opposition and a genealogical interpretation. The results show that the text under study represents the ecological crisis as a long-term, intergenerational threat, reveals global injustice in climate issues, and reveals the power-knowledge mechanisms behind the production of scientific knowledge and environmental policy. Furthermore, a cosmic perspective is presented through the astrobiological concept of the Anthropocene, which emphasizes human limitations and the importance of "thinking like a planet." It also functions as a counter-discourse that reveals the ecological regime of anthropocentric truth while simultaneously building a new consciousness based on justice, moral responsibility, and desire.